Crossing the point of no return: A public goods experiment - Urs Fischbacher; Werner Güth; M. Vittoria Levati (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Participants in a public goods experiment receive private or common signals regarding the so-called point of no return, meaning that if the group's total contribution falls below this point, all payoffs are reduced. An individual faces the usual conflict between private and collective interests above the point of no return, while he incurs the risk of damaging everyone by not surpassing the point. Our data reveal that contributions are higher if the cost of not reaching the threshold is high. In particular if the signal is private, many subjects are not willing to provide the necessary contribution.
Keywords: H41; C92; C72; 330; public goods; provision point mechanism; experiments; reduction factor; signal; Öffentliches Gut; Nichtkooperatives Spiel; Signalling; Test